O coração do faraó no livro do Êxodo e na tradição judaica - Gross, Fernando (2017)
The study presented here welcomes literary and historical-theological motif belonged to the biblical narrative on the exodus. Repeatedly, that is, in fourteen scenes, the texts of the book of Exodus refer to the "heart of the pharaoh", which is mentioned twenty times. In ten moments, it is described how the Lord, the God of Israel, acts with the heart of the pharaoh (Ex 4,21; 7,3; 9,12,14; 10,1,20,27; 11,10; 14,4,8). In four moments, it is contemplated how the pharaoh leads with his heart (Ex 7,23, 8,11,28; 9,34). And in six other moments, it is narrated how the heart of the pharaoh reacts to the events (Ex 7,13,14,22; 8,15; 9,7,35). Moreover, different verbs indicate different movements of the pharaoh's heart. Thus, the study presented in this Dissertation seeks to understand, in its first part, what the biblical narrative reflects on the heart of who ruled Egypt. In the second part, the present study analyzes how the Jewish tradition, throughout the history, continued the reflection on the heart of the pharaoh